Beyond #NotTooYoungToRun: party candidacy, political representation and legislative effectiveness of young politicians in Nigeria’s Fourth Republic - Abati, Omomayowa Olawale (Stellenbosch : Stellenbosch University, 2024)
Thesis (DPhil)--Stellenbosch University, 2024.